Somatic rearrangements forming active immunoglobulin mu genes in B and T lymphoid cell lines. - Cory, S (1980)
We have cloned an active gene for an immunoglobulin mu heavy (H) chain, bearing the variable (VH), joining (JH), and constant (C mu) sequences expressed in the IgM-secreting mouse plasmacytoma HPC-76. The mu gene was formed by somatic recombination between a VH gene and one of several JH genes, which are located about 7.7 kilobase pairs from the C mu gene in embryo DNA. The JH-C mu intervening sequence has suffered a deletion of about 2.7 kilobase pairs in HPC-76. Because the delection encompasses sequences required to switch an expressed VH-JH gene from C mu to another CH gene, it may represent a mechanism for "freezing" a lymphocyte clone at the stage of IgM expression. For the second (inactive) C mu allele in HPC-76, the entire joining and switch regions have been deleted; functional inactivation of one allele may thus represent one mechanism by which a lymphocyte clone restricts expression to a single allele (allelic exclusion). Probes generated from the cloned mu gene allowed examination of the JH locus in B, Abelson "pre-B," and T lymphoma cell lines and a myeloid line, all of which cotain RNA species bearing C mu sequences. The B and pre-B lines exhibited recombination within both alleles of the JH locus, suggesting that both alleles may be expressed in some cells. The absence of the JH gene 5' to the recombination sites favors a deletion mechanism for VH-JH joining. Recombination within the JH locus was also detected in two out of four T lymphoma lines, but not in the myeloid line. This indicates that the mechanism by which B cells generate immunoglobulin diversity is operational in some T cells. Lines that synthesize mu RNA without JH rearrangement may have activated the C mu gene directly or have undergone recombination at a more distant locus.